2021
DOI: 10.1101/2021.04.22.440930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquitination of G3BP1 mediates stress granule disassembly in a stress-specific manner

Abstract: Stress granules are dynamic, reversible condensates composed of RNA and protein that assemble in response to a variety of stressors and are normally disassembled after stress is removed. Whereas the composition of stress granules and the mechanisms underlying their assembly have been extensively studied, far less is known about the mechanisms that govern disassembly. Impaired disassembly has been implicated in some diseases. Here we report that stress granule disassembly is context-dependent and, in the settin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…To prior efforts of how de-mixing RNA/RBP condensates are disassembled in cells 23,111,112 , our demonstration that HSPB1 facilitates disassembly of TDP-43 de-mixed droplets (Figure 5) offers what we believe is strong evidence for the proposal that binding of HSPB1 to TDP-43 in gel/solid structures acts to maintain TDP-43 in a refolding-capable state that facilitates its refolding. After removal of a provoking stress and restoration of ATP levels, it enhances droplet resolution (Supplemental Figure 11; Figure 7g) acting in conjunction with the HSP70 family chaperones, BAG2, BAG3, and HSP40 (e.g., DNAJB1 but not DNAJA1 [in line with recent report of the unique function DNAJB family proteins 113 ]).…”
Section: Discussionmentioning
confidence: 55%
“…To prior efforts of how de-mixing RNA/RBP condensates are disassembled in cells 23,111,112 , our demonstration that HSPB1 facilitates disassembly of TDP-43 de-mixed droplets (Figure 5) offers what we believe is strong evidence for the proposal that binding of HSPB1 to TDP-43 in gel/solid structures acts to maintain TDP-43 in a refolding-capable state that facilitates its refolding. After removal of a provoking stress and restoration of ATP levels, it enhances droplet resolution (Supplemental Figure 11; Figure 7g) acting in conjunction with the HSP70 family chaperones, BAG2, BAG3, and HSP40 (e.g., DNAJB1 but not DNAJA1 [in line with recent report of the unique function DNAJB family proteins 113 ]).…”
Section: Discussionmentioning
confidence: 55%
“…Notably, in addition to eIF4A, other ATPases have also been shown to regulate SG dynamics. For example, recent studies have suggested a role for VCP, an AAA ATPase functioning as a segregase, in eliminating SGs through either the ubiquitin-proteasome or autophagy pathway 14,72 . Thus, reductions in ATP levels may regulate eSG/SG dynamics by affecting additional ATPases.…”
Section: Discussionmentioning
confidence: 99%
“…UBQLN2 expression levels are negatively correlated to the number and sizes of stress granules (Alexander et al, 2018), indicating a role for UBQLN2 in regulating the disassembly of stress granules. Stress granules are cleared either following the removal of K63-linked polyubiquitinated G3BP1, a stress granule core protein, or by autophagy, depending on the stressor types and length of exposure (Buchan et al, 2013;Gwon et al, 2021). Through differential modulation of UBQLN2 LLPS by different polyUb chains, UBQLN2 may facilitate these different stress granule clearance processes (Fig.…”
Section: Discussionmentioning
confidence: 99%